Local structure of Fe2+ and Fe3+ in organic solvents. (1st November 2022) - Inoue, Dai; Komatsu, Toshiki; Niwa, Hideharu; Nitani, Hiroaki; Abe, Hitoshi; Moritomo, Yutaka
Abstract: We systematically investigated the local structure of Fe 2+ and Fe 3+ in 11 solvents by extended X-ray absorption fine structure (EXAFS) analysis and X-ray absorption near-edge structure (XANES). The EXAFS analyses with a one-shell model indicate that Fe 2+ and Fe 3+ are coordinated by six oxygen of the ligand molecules ( L ) and form a Fe L 6 -type complex in all solvents. The XANES suggests that the [Fe L 6 ] 3+ complex shows noncentrosymmetric deformation in several solvents. In protic solvents, the EXAFS analyses with a two-shell model revealed that the coordination number ( n C ) of the second nearest carbon around Fe 3+ significantly depends on L . We interpreted the observation in terms of the distribution of the Fe-C distance.